PENGARUH PEMBERIAN PUPUK UREA, KOMPOS DAN KOMBINASINYA TERHADAP PERTUMBUHAN DAN PRODUKSI RUMPUT GAJAH MINI (PENNISETUM PURPUREUM CV. MOTT): The Effect of Fertilizing Urea, Comost and its Combinations on The Growth and Production of Dwarf Elephant Grass (Pennisetum purpureum Cv. Mott) - M. Chaedir; Budiman Nohong; syamsuddin Nompo (Buletin Nutrisi dan Makanan Ternak, 2021)
Growth and Production of Mini Elephant Grass (Pennisetum purpureum cv. Mott) Given Compost, Urea, and Their Combination Fertilizer. In Indonesia, land that is often used to plant mini elephant grass is marginal land. Therefore, technological innovation is needed to improve the growth and production of mini elephant grass. One of the efforts that can be done to increase the growth and production of mini elephant grass is by providing fertilizer. This study aims to determine the growth and production of mini elephant grass given by compost, urea, and its combination. This study used a completely randomized design (CRD) consisting of 4 treatments and 4 replications namely P0: No fertilizer, P1: Compost fertilizer 40ton/ha = 200 g/Polybag, P2 : Urea fertilizer 250 kg/ha = 1.25 g/polybag and P3 : Compost and Urea fertilizer, namely (P1) + (P2) = 100 g/polybag + 0.625 g/ polybag. The application of compost and urea in the P3 treatment had a significant effect (P<0.05) on plant height (cm) of 85.75 and dry matter production (g/polybag) of 22.37. The application of urea fertilizer in the P2 treatment had a significant effect (P<0.05) on the number of tillers (stems/polybags) of 2.25. Based on the results of the study, it was concluded that the provision of compost and urea gave good results on plant height, a number of tillers, and dry matter production of mini elephant grass plants. Keywords: Compost, Elephant Grass, Fertilizer, Marginal Land, and Urea.